2013
DOI: 10.3189/2013jog12j147
|View full text |Cite
|
Sign up to set email alerts
|

Antarctica, Greenland and Gulf of Alaska land-ice evolution from an iterated GRACE global mascon solution

Abstract: ABSTRACT. We have determined the ice mass evolution of the Antarctic and Greenland ice sheets (AIS and GIS) and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
412
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 380 publications
(426 citation statements)
references
References 66 publications
(115 reference statements)
14
412
0
Order By: Relevance
“…Leakage error in GRACE estimates can also be reduced by using high-resolution mascon solutions that are derived either directly from GRACE satellite range and range rate measurements (Rowlands et al 2005;Luthcke et al 2013) or from GRACE spherical harmonic solutions (Jacob et al 2012;Schrama et al 2014). Please note that forward modeling can be regarded as a mascon approach using GRACE spherical harmonic solutions and is solved in the spatial domain, as compared to the spherical harmonic domain (e.g., Jacob et al 2012).…”
Section: Uncertainties In Grace Tws Storage Changesmentioning
confidence: 99%
“…Leakage error in GRACE estimates can also be reduced by using high-resolution mascon solutions that are derived either directly from GRACE satellite range and range rate measurements (Rowlands et al 2005;Luthcke et al 2013) or from GRACE spherical harmonic solutions (Jacob et al 2012;Schrama et al 2014). Please note that forward modeling can be regarded as a mascon approach using GRACE spherical harmonic solutions and is solved in the spatial domain, as compared to the spherical harmonic domain (e.g., Jacob et al 2012).…”
Section: Uncertainties In Grace Tws Storage Changesmentioning
confidence: 99%
“…Previous studies have shown large negative mass imbalances and significant elevation losses for the nAP (Ivins et al, 2011;Shepherd et al, 2012;Luthcke et al, 2013;Sasgen et al, 2013;McMillan et al, 2014). However, in general these studies have not resolved the spatial distribution of mass imbalance in detail.…”
Section: Introductionmentioning
confidence: 88%
“…Glacier basins 1a,4a,6a,and 12a;c Glacier basins 19,[21][22][23][24][25]26b,[27][28][29][30]and 31a;d Glacier basins 17,18,and 19;e Our mass balance estimate for the nAP region agrees well with recently published gravimetric values. Recent GRACEbased estimates that can be most easily compared with our study yield values of −27.5 ± 10 Gt a −1 (summing the mascons encompassing and adjacent to our study area) (Luthcke et al, 2013), and 26 ± 3 Gt a −1 for a larger GRACE mascon extending to 70 • S (Sasgen et al, 2013). Due to the low spatial resolution of the gravimetric measurement, both these GRACE-derived results inherently include portions of the Larsen C ice shelf and adjacent ice-covered islands we did not measure (notably, King George Island) that lost elevation and mass during the ICESat period (Gardner et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…comm., 2014) of −144 ± 28 Gt/years for Greenland and −123 ± 28 Gt/years for Alaska are in closer and worse agreement, respectively. Luthcke et al (2013) used a GRACE mascon approach to infer total mass loss of −71 ± 11 Gt/years in Alaska and −226 ± 12 Gt/years for Greenland. Shepherd et al (2012) also inspected the Greenland ice sheet and estimated a mass loss of −142 ± 49 Gt/years which broadly matches our result.…”
Section: Mass Loss Estimatesmentioning
confidence: 99%